IMPLEMENTASI PELATIHAN KOMPUTER PADA WARGA BELAJAR PENDIDIKAN KESETARAAN PAKET C DALAM MENGHADAPI PENDIDIKAN DI ERA GLOBALISASI - Nanda Afifah Oktovi Hidayat; Safuri Musa; Nia Hoerniasih (Comm-Edu (Community Education Journal), 2023)
This research was conducted to answer the existing conflicts regarding the implementation of Community Education programs, especially in computer training programs to increase the knowledge and skills of learning citizens. Based on this research, it is hoped that it can provide input to the organizers of one of the Community Education Programs or non-formal education when they are looking for alternatives when implementing a program that can empower residents or communities around PKBM. therefore the aims of this study include: (1) to describe the computer training process for citizens learning Equality Education package C in the face of the globalization era, (2) to describe the supporting and inhibiting factors of the computer training process for citizens learning Equality Education package C in dealing with globalization era. This research uses a qualitative approach with descriptive methods. The subjects in this study consisted of the Head of PKBM, residents studying package C. Tutors. Data analysis was carried out using data reduction techniques, data presentation, and drawing conclusions. The results of the research are as follows: (1) the personal computer training at PBM Talent Semesta has been able to increase the knowledge of the learning residents; (2) the skills of the learning residents in the field of computers at this PKBM have been able to keep up with technological developments that are increasing rapidly skyrocketing from day to day; (3) can increase their self-confidence when one day they go directly to the community. However, during the implementation of the training there were obstacles, namely (1) Lack of learning tools or media such as laptops or computersÂ